Microbial Spectrum, Intraoperative Findings, and Postoperative Outcomes in Native Knee Joint Infections: A Retrospective Analysis - Jonas Roos; Britta Mangels; Max Jaenisch; Matthias Dominik Wimmer; Thomas Martin Randau; Christian Prangenberg; Kristian Welle; Martin Gathen (Clinics and Practice)
Background: Native knee joint infections, while uncommon, present a serious condition predominantly instigated by bacteria such as Staphylococcus aureus. Without timely intervention, they can result in joint destruction or sepsis, with risk factors encompassing preexisting medical conditions and iatrogenic procedures. The diagnostic process includes a comprehensive patient history, clinical evaluation, laboratory testing, imaging studies, and microbiological investigations. Treatment typically involves joint aspiration and arthroscopy. This study aims to examine and establish correlations between diagnostic criteria and treatment modalities, enhancing the speed and specificity of future therapeutic strategies. Materials and methods: The present study is a retrospective cohort study conducted at a 1200-bed university clinic between 2007 and 2017, with an in-depth examination of patient details, symptoms, treatments, and outcomes. A scoring system was developed to classify the severity of knee joint impairment, categorizing patients on the basis of hospital stay duration, surgeries, and postoperative factors such as recurring symptoms, pain, and range of motion. Results: This study of 116 patients with knee joint infections revealed that clinical symptoms such as pain, swelling, and effusion are common but not definitive for diagnosis. Laboratory analysis revealed no significant differences in CRP or leukocyte counts between cultures positive or negative for pathogens. Hospital stay and disease severity are influenced by factors such as age, sex, presence of polyarthritis, neutrophil count, and type of pathogen, with higher weight and cortisone treatment associated with poorer outcomes. Conclusions: This study highlights the diagnostic challenges in native knee joint infections, revealing the need for comprehensive approaches given the nonspecificity of clinical symptoms and laboratory findings. This underscores the importance of advancing research through standardized methodologies and prospective studies to increase the accuracy of diagnosis and the effectiveness of treatment in this field.